Виробництво полив'яного посуду в Криму за часів Улуг Улусу - Тесленко, І.Б. (Археологія і давня історія України, 2018)
У роботі розглянуто питання, пов'язані з виробництвом глазурованого посуду в Тавриці за часів
Джучидської держави і генуезької колонізації. Для
дослідження залучаються матеріали археологічних розкопок XX та перших десятиліть XXI ст.,
застосовуються сучасні підходи до аналізу великих
обсягів кераміки, а також залучаються результати вивчення окремих груп виробів археометричними методами. Different questions related to the manufacturing of
glazed pottery in Taurica during the Jochid state and the Genoese colonization are in the sphere of scientists’
interests for more than a century. Significant increase of the archeological collections in the last decades of
the 20th and beginning of the 21st century, together with the more progressive approaches to the analysis
of large volumes of ceramics, and the using of archeometrical methods, allow to reach a new level of study in this field.
Now on the territory of the Crimea are known at least 10 pottery workshops, which have appeared at
different times in the period from the last quarter of the 13th (not earlier than the end of the 1260s) to the
first quarter of the 15th century and 6 site with single evidence of such manufacturing. 9 workshops were located
in five medieval town of the peninsula: 2 — in Kaffa (Theodosia), 2 — in Soldaya (Sudak), at least 2 —
in Solhat (Staryi Krym), one in Lusta (Alushta) and in Chambalo (Balaklava). Two more workshops (the earliest
ones among known) were found at the settlement of the potters Bokatash II in Solkhat vicinity. Visual, and
in some cases archeometrical characteristics of their products were determined. So it became possible to estimate
the volumes of the glazed pottery manufacturing of various regions of the peninsula (South-Eastern
and South-Western Crimea), as well as the individual workshops, in particular in Alushta, Balaklava and
Bokatash. In addition, it allowed to determine the geography, volume and dynamics of the trade by glazed
pottery from Crimea. The last one began to form an appreciable
part of the ceramic assemblages outside the peninsula from around the 1320s.
At the beginning of the glazed ceramics production in Taurica the distinction in cultural traditions among
the workshops were well visible. Some of them presumably may indicate the origin of the craftsmen from the
territory of Anatolia, Transcaucasia, the Eastern Mediterranean, the Balkans, and possibly Central Asia, and
may be even Italy. Subsequently, around the last third of the 14th century, this individuality is gradually replaced
by standardization of production. The leader in this craft became the Genoese trading posts, headed by Caffa.